Global Statistics of Ice Microphysical and Optical Properties at Tops of Optically Thick Ice Clouds. Issue 6 (12th March 2020) - van Diedenhoven, Bastiaan; Ackerman, Andrew S.; Fridlind, Ann M.; Cairns, Brian; Riedi, Jérôme
Abstract: The sizes and shapes of ice crystals in clouds affect fundamental microphysical processes, such as sedimentation and aggregation, as well as their optical properties. The evolution of ice crystal size and shape depends on temperature and supersaturation, as well as on other processes that may lead to various coexisting complex shapes. Here we present a global assessment of collocated size and shape characteristics and shortwave scattering properties of ice crystals at the tops of optically thick clouds inferred from space‐borne multiwavelength reflectance measurements and multiangle polarimetry. The results indicate systematic covariations of ice size, shape, and distortion, as well as variations with temperature that can be plausibly related to simplified ice crystal growth theory and in situ and laboratory data. This simplicity may be attributable to the temperature dependence of cloud top ice size and shapes commonly being dominated by vapor growth at conditions similar to those at cloud top. Such a conclusion may be viewed as somewhat surprising given the expectation that ice properties at cloud top will be an integral manifestation of processes occurring at lower levels within updrafts. We also find that, contrary to commonly used models, ice scattering asymmetry parameters decrease with increasing effective radius, reducing sensitivity of cloud reflectance to particle size. Plain Language Summary: The sizes and shapes of ice crystals in cold clouds influence how these clouds evolve and how much sunlight they reflect. It is relatively well understood how temperature and humidity affect the sizes and shapes of ice crystals as they grow directly from water vapor. However, our understanding of the influence of other complex processes on ice crystal shape and size in natural clouds is less developed. Using combined measurements of two satellites, we investigate the variation of sizes and shapes in the tops of thick ice clouds on a global scale. We find that how observed ice crystal size and shape varies with temperature can be well explained by the theory on ice crystals growing from water vapor. This simplicity is somewhat surprising and may indicate that the many more complex ice growth processes have limited effect on the variation of ice shape and size at the tops of clouds. The analysis also suggests that some common assumptions on the influence of ice crystal size and shape on the amount of sunlight that is reflected by ice clouds need to be revisited. Our results can serve as a reference for improving the representation of ice clouds in climate models. Key Points: We present a global assessment of collocated cloud top ice size, shape, and scattering property observations Ice scattering asymmetry parameters are found to decrease with increasing effective radius, contrary to commonly used optical models The observations suggest that the temperature dependence of cloud top ice size and shapes are commonly dominated by vapor growth processes